ECONOMY NETWORKS IN DEVELOPMENT INNOVATIVE INVESTMENT ACTIVITY INCREASE METHODICAL BASICS - Karajanova Gulnoza Tolliyevna (International Journal of Economic Integration and Regional Competitiveness, 2024)
The dynamic intersection of economic growth and innovative investments plays a critical role in modern development strategies, particularly as global competition intensifies. Innovative investment drives technological advancement and supports strategic initiatives like technological parks and clusters, which contribute significantly to national economic resilience and competitive positioning. However, many regions, such as Ukraine, face limited institutional support, restricting their potential for robust innovation ecosystems. Despite the evident link between innovation and economic development, there is a need for integrated frameworks that harmonize investment strategies across sectors and facilitate cross-industry synergies. This study aims to investigate the theoretical foundations and practical strategies that enable successful innovative investments, emphasizing sectoral approaches and stable economic growth. Findings reveal that targeted investments in SMEs, digital transformation, and public-private collaborations can catalyze significant economic and social progress. By synthesizing classical and modern theories, this study provides a comprehensive methodological basis for effective innovation investments across diverse economic networks. Policymakers and industry leaders are encouraged to adopt multi-faceted investment approaches that foster stable ecosystems and support long-term economic growth, particularly through cooperative, sector-wide initiatives.